2015
DOI: 10.1063/1.4921071
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fibrillization of Alzheimer’s amyloid-β peptide (1-42)

Abstract: The amyloid deposition in the form of extracellular fibrillar aggregates of amyloid-β (Aβ) peptide is a critical pathological event in Alzheimer’s disease. Here, we report a systematic investigation of the effects of environmental factors on the kinetics of Aβ fibrillization in vitro. The effects of Aβ42 peptide concentration, temperature, pH, added solvents and the ratio of Aβ40 and Aβ42 on the peptide fibrillization under agitated conditions was studied. The analysis show that the rate of fibril growth by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 39 publications
5
49
0
1
Order By: Relevance
“…Structural and metal‐binding studies have demonstrated that the metal binding to Aβ peptides is at large extent determined by His residues located in positions 6, 13 and 14 of human Aβ [2‐3,5,6]. Replacement of His13 with Arg in rat Aβ peptide is assumed to be responsible for its lower sensitivity towards Zn(II)‐induced aggregation as compared with human Aβ [7].…”
Section: Figmentioning
confidence: 99%
“…Structural and metal‐binding studies have demonstrated that the metal binding to Aβ peptides is at large extent determined by His residues located in positions 6, 13 and 14 of human Aβ [2‐3,5,6]. Replacement of His13 with Arg in rat Aβ peptide is assumed to be responsible for its lower sensitivity towards Zn(II)‐induced aggregation as compared with human Aβ [7].…”
Section: Figmentioning
confidence: 99%
“…(a) The Aβ 1-42 dimer obtained by modelling studies based on the SAXS data for the stoichiometric Aβ 1-42 complexes with 8-hydroxyquinolines [ 200 ]; (b) The FP i plot shows the anticipated ‘strand’ configurations in the Aβ homodimer at pH 5-6 i.e. under the conditions that accelerate fibrillization (light blue curve H + /E − , blue curve H + /E 0 ) [ 203 , 204 ]; (c) The antiparallel coiled coil as a model of Aβ dimer structure: the favoured antiparallel dimerization of Aβ in aqueous solutions matches the CHC and C-terminal segments that both adopt either the C 7eq or C 5 conformations. The antiparallel assembly could in addition be stabilized by H-bonding between the segments of consecutive ‘turns’ V24-G37 which may adopt the C 5 * fold in the dimer.…”
Section: Resultsmentioning
confidence: 99%
“…Fig 22B(b) shows the ‘strand’ configurations in the homodimer that favor fibrillization [ 203 , 204 ]. The sequence β0(C 7eq )-β1(C 5 )-β2(C 5 *)-β3(C 5 ) is crucial to the FP -directed molecular recognition in dimerization and subsequent pleiomorphic behavior of Aβ.…”
Section: Resultsmentioning
confidence: 99%
“…One of the observations is that A aggregation is a modifiable process. Environmental factors, such as peptide concentration, temperature, pH, ion strength, added solvents, agitation, etc., have been studied and are known to affect A fibrillization 9 . A great variety of molecules, chemical and biological, are able to modify as well the aggregation of A.…”
Section: ) Introductionmentioning
confidence: 99%